The Role of Leaders in Reducing Role Ambiguity to Enhance Employee Motivation and Commitment: A Study Among School leaders and Staff in Al Ain Schools - ALDHAERI, ALYAZYA (2024)
The influence of role ambiguity and leadership on employee motivation and commitment is widely reported. With rapid organizational change in UAE schools under the educational reforms and aspirations to participate in the knowledge economy, this study seeks to examine the role of leaders in Al Ain public schools in mitigating the negative impact of role ambiguity on employee dedication and motivation. Reviewing existing literature suggests a conspicuous dearth of empirical evidence on the impact of role ambiguity on employee motivation and commitment in UAE’s educational setting. Therefore, these variables and their impact is examined within the domain of Al Ain public schools. This study investigated the involvement of public-school leaders in relation to the adverse impact of role ambiguity on employee commitment and motivation amidst organizational transformation. A mixed method research design is used to collect substantial data that would yield insights into the variables under study. Data is collected through interviews and surveys administered to employees of selected public schools. Statistical and interpretative techniques are used for data analysis. Based on analysis of the collected data, the study revealed that leaders play a significant role in moderating the influence of uncertainty on employee motivation and commitment. The research indicates that leadership of schools can alleviate the adverse impacts of role ambiguity on the motivation and commitment while the organizations are transforming and seeing constant changes. Keywords: Role Ambiguity, Employee Motivation, Employee Commitment, School Leadership, Al Ain, UAE